2017
DOI: 10.1186/s12873-017-0150-5
|View full text |Cite
|
Sign up to set email alerts
|

Safety and applicability of a pre-stage public access ventilator for trained laypersons: a proof of principle study

Abstract: BackgroundContemporary resuscitation guidelines for basic life support recommend an immediate onset of cardiac compressions in case of cardiac arrest followed by rescue breaths. Effective ventilation is often omitted due to fear of doing harm and fear of infectious diseases. In order to improve ventilation a pre-stage of an automatic respirator was developed for use by laypersons.MethodsFifty-two healthy volunteers were ventilated by means of a prototype respirator via a full-face mask in a pilot study. The pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…There has already been some effort in developing low-cost ventilators in the literature [62] , [63] , [64] , [65] , [66] , [67] , [68] , [69] , [70] as well as in the maker community; however, the former failed to provide full source code and the latter (as of March 2020) was unvalidated and largely untested [71] . To both fill the current critical need for ventilators as well as provide a basis for future pandemics, this article provides the full source code for a fully-functional low-cost 3-D printable open-source pandemic ventilator and includes validation testing using an artificial lung.…”
Section: Hardware In Contextmentioning
confidence: 99%
“…There has already been some effort in developing low-cost ventilators in the literature [62] , [63] , [64] , [65] , [66] , [67] , [68] , [69] , [70] as well as in the maker community; however, the former failed to provide full source code and the latter (as of March 2020) was unvalidated and largely untested [71] . To both fill the current critical need for ventilators as well as provide a basis for future pandemics, this article provides the full source code for a fully-functional low-cost 3-D printable open-source pandemic ventilator and includes validation testing using an artificial lung.…”
Section: Hardware In Contextmentioning
confidence: 99%
“…A recent review of open source ventilators was completed in the midst of the COVID-19 pandemic [138] which found that the peer-reviewed and vetted systems [139][140][141][142][143][143][144][145] lacked complete documentation and the "open source" ventilator systems that were documented [146] were either at the very early stages of design (often without a prototype) and lacked testing, or only had basic testing. This is changing rapidly with AmboVent releasing all plans [147], and there are several projects like the OxyGEN [148], an automated manual ventilator, being tested that appear to be at or near the point of production for use in hospitals.…”
Section: Ventilatorsmentioning
confidence: 99%
“…The estimated price of manufacturing this device is less than $200. A pre-stage public access ventilator (PAV) [ 59 ] is designed with a turbine and sensors. The developed prototype can detect leakage and airway occlusion using the signals from sensors.…”
Section: Breathing Aid Devices For Covid-19 Patientsmentioning
confidence: 99%